2004
DOI: 10.1097/01.mph.0000140653.50344.5c
|View full text |Cite
|
Sign up to set email alerts
|

Viral Infections in Juvenile Myelomonocytic Leukemia: Prevalence and Clinical Implications

Abstract: Viral infection may be present in two thirds of children with newly diagnosed JMML, but it does not constitute a basis for revising clinical management. The possibility that EBV or other viruses contribute to JMML pathogenesis by stimulating pre-exiting malignant clones warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…It is reported that viral infections including CMV mimic JMML. [16][17][18][19] As concomitant viral infections are often noted in JMML patients, it is not straightforward to distinguish them from JMML. In the patient reported here, CMV antigenemia was detected only once without any additional clinical symptoms and there was no significant change in the clinical features before and after the detection of CMV antigenemia or administration of ganciclovir; therefore, we believe that CMV did not play a central role in the pathogenesis in this patient.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that viral infections including CMV mimic JMML. [16][17][18][19] As concomitant viral infections are often noted in JMML patients, it is not straightforward to distinguish them from JMML. In the patient reported here, CMV antigenemia was detected only once without any additional clinical symptoms and there was no significant change in the clinical features before and after the detection of CMV antigenemia or administration of ganciclovir; therefore, we believe that CMV did not play a central role in the pathogenesis in this patient.…”
Section: Discussionmentioning
confidence: 99%
“…[79][80][81][82] A search for clinical evidence of either neurofibromatosis type 1 and/or Noonan syndrome should be conducted in the patient and in family members. Both of these genetic conditions can occur in either heritable or sporadic forms.…”
Section: Jmmlfpathogenesismentioning
confidence: 99%
“…Toyoda H et al [8], presented a case of CMV infection coexistent with JMML, using high fidelity investigations to assess clonality as well as CMV antigen presence. A prospective study by Manabe A et al [9], evaluated 18 patients diagnosed as JMML (International JMML Working Group) for concurrent viral infection by measuring the cellular expression of the MxA protein. This is a reliable marker of viral infection .…”
Section: Discussionmentioning
confidence: 99%